ANALISIS KUALITAS LAYANAN 4G LTE KAWASAN EKONOMI KHUSUS MANDALIKA MENGGUNAKAN METODE DRIVE TEST DAN ATOLL - Putu Aditya Bayu Trana Suta; Endah Budi Purnomowati; Sapriesty Nainy Sari (Jurnal Mahasiswa TEUB, 2022)
Drive test is a measurement method that is carried out on a mobile basis to observe the quality of telecommunication network services. The drive test measurement was carried out using the GNetTrack Pro. Meanwhile, eNodeB analysis was performed using atoll software. This study aims to determine and analyze the quality of 4G LTE network services in the Mandalika Special Economic Zone, Central Lombok Regency using the RSRP and RSRQ parameters. The results of this study indicate that the RSRP value in the Mandalika Special Economic Zone which is more than -80 dBm is only 28.3%. Meanwhile, the highest value is between -95 dBm to -80 dBm, which is 47.6%. This value indicates that the transmit power of the transmitted signal is in the good category, but does not meet the very good criteria according to the KPI standard, which is above -80 dBm, the most RSRQ value in the Mandalika Special Economic Zone is between -14 dB. up to -9 dB that is equal to 65.4%. This value indicates the quality of the received signal is in the normal category. And there is no RSRQ value above -3 dB, and based on the coverage, the more eNodeB, the wider the signal coverage area, but will also allow a higher probability of interference.Keywords: Special Economic Zones, Drive Test, RSRP, RSRQ, ATOLL